Polarization switching in quasiplanar BiFeO3 capacitors - You, Lu (2011)
Polarization switching in multiferroic BiFeO3 is studied using a quasiplanar capacitor geometry. Macroscopic quantitative hysteresis measurements using single-pair electrodes yield results that agree well with the theoretical predictions. Nanoscale ferroelectric domain analyses reveal that highly aligned 71° stripe domains are created upon electrical switching. Careful reconstruction of the polarization configuration demonstrates that in-plane polarization reversal is achieved by a coherent 71° switching mechanism, consistent with the macroscopic measurement results. Such control of polarization switching in quasiplanar BiFeO3 capacitors is crucial for the electrical control of the multifunctionality of BiFeO3.